Cortisol regulates neonatal lung development via Smoothened - Shanshan Lu; Yifei Chen; Jiawen Song; Liangliang Ren; Jun Du; Donglai Shen; Jiayin Peng; Yao Yin; Xia Li; Yuqing Wang; Yan Gao; Siman Han; et al. (Respiratory Research)
Abstract Background Neonatal respiratory distress syndrome (NRDS), one of the main causes of neonatal death, is clinically characterized by progressive dyspnea and cyanosis 1 to 2 h after birth. Corticosteroids are commonly used to prevent NRDS in clinical. However, the protective mechanism of the corticosteroids remains largely unclear. Methods In this study, the simulation of the molecular docking by Autodock, in vitro binding experiments, and Sonic Hedgehog (SHH) pathway examination in cells were performed to study the directly binding of cortisol to Smoothened (SMO). To explore the effect of cortisol action on the SHH pathway on neonatal lung development, we generated a genetic mouse, in which leucine 116 (L112 in human) of SMO was mutated to alanine 116 (L116A, Smo a/a ) by the CRISPR-Cas9, based on sequence differences between human and mice. Then, we performed morphological analysis, single-cell RNA sequencing (scRNA-seq) on lung tissue and fluorescence in situ hybridization (FISH). Results In this study, we reported that cortisol, the endogenous glucocorticoid, inhibited the sonic hedgehog (Shh)/SMO-mediated proliferation of lung fibroblasts to maintain the normal lung development. Specifically, cortisol competed with cholesterol for binding to the cysteine-rich domain (CRD) in SMO to inhibit the activation of Shh/SMO signaling, a critical signaling known for cell proliferation. Cortisol did not inhibit the activation of SMO when L112 in its CRD was mutated to A112. Moreover, Smo a/a (L116A) mice exhibited the immature lungs in which over-proliferation of interstitial fibroblasts and reduction in the surfactant protein were evident. Conclusion Together, these results suggested that cortisol regulated cholesterol stimulation of SMO by competitively binding to the CRD to regulate neonatal lung maturation in mice.